The impact of redeployment on teacher performance in Maune Circuit Department of Education Limpopo. - Ledwaba, Lesetja Peter (My University, 2007)
Refer to document
Thesis (M.Dev.) --University of Limpopo, 2007
Keywords: Teacher redeployment; Teacher transfer -- South Africa -- Limpopo; Teacher -- job satisfaction